Empowering Indonesia's Nursing Workforce: A Pillar for Achieving Golden Indonesia 2045 - Ferry Efendi (Asosiasi Institusi Pendidikan Ners Indonesia (AIPNI), 2024)
competitive nation by 2045, the nursing workforce plays a pivotal role in realizing this ambition (Efendi, 2024). Nurses form the backbone of the healthcare system, ensuring the delivery of quality care to communities across the archipelago (WHO, 2021). While Indonesia currently has a temporary surplus of nurses, this presents a strategic opportunity to compete in the global nursing labor market (Efendi et al., 2024). However, succeeding in this competitive arena requires critical investments in areas such as language proficiency, readiness to adapt to diverse healthcare systems, and mental preparation for working overseas (Pradipta et al., 2023).A resilient and globally competitive nursing workforce can drive transformative health sector reforms, directly contributing to the realization of Golden Indonesia 2045. Nurses trained for international roles can also return to Indonesia, bringing back valuable skills and experiences to strengthen the local healthcare system. This cyclical benefit underscores the importance of policies facilitating international mobility, such as streamlined licensing and certification processes. Additionally, partnerships with foreign governments and institutions are critical to ensure ethical recruitment practices and the protection of migrant nurses' welfare.To support Golden Indonesia 2045, the government and stakeholders must prioritize comprehensive strategies to strengthen the nursing workforce. Key initiatives should include scaling up nurse education and training programs to align with international needs, enhancing workforce planning to address global demand, and establishing robust career development pathways to retain skilled nurses. By addressing these challenges, Indonesia can build a resilient and globally competitive nursing workforce, capable of advancing health sector reforms, contributing to human capital development, and supporting the nation's overarching goal of inclusive and sustainable progress.